(untitled) (Third Sector Social Economic Review, 2014)
State is unique organisation of under the authority of an institution that responds to the needs of the people are knitting. As stated in the Constitution of the road should be the welfare state as well as central administration, local government units formed by the solution to people’s needs and be prepared to the implementation of social policies that passes. The policies developed under the concept of subsidiarity by local government units, especially by municipalities is easier to find opportunities to apply. Social municipality is especially with socially weak, needy, and also to individuals who are homeless children, women, the elderly, adults, people with disabilities are produced retrospectively policies, measures and services are offered. In this article the theoretical and practical aspects of social municipality are discussed.